Development of pastoral administrative leadership scale based on the theories of educational leadership - Sung Joong Kim (Cogent Business & Management, 2019)
With increased interest in the concept of leadership, there is a need to examine its various types in terms of scale, necessity, as well as importance. This study thus attempted to measure pastoral administrative leadership with the objective of revealing the necessity and importance of studying this type of leadership in particular, as well as to develop its own measurement scale. To make the survey questionnaire, five key dimensions of pastoral administrative leadership (instructional method, decision-making process, communicative method, church culture, and church structure) were subsequently selected, based on suggestions from scholars in educational leadership. For this study, the population was comprised of full-time senior pastors of churches in South Korea. A total sample of 1,000 was then selected through a convenience sampling of Korean pastors. Through the factor analysis [exploratory factor analysis (EFA) and confirmatory factor analysis (CFA)] results, it was verified that the items of this survey questionnaire were able to measure pastoral administrative leadership. Using these results as the basis, this research developed a measurement scale, the Scale of Pastoral Administrative Leadership (SPAL). As such, this study can be the starting point in measuring administrative-focused pastoral leadership.
Keywords: 650; pastoral administrative leadership; educational leadership; measurement scale; church; church administration